Constructing nickel vanadium phosphide nanoarrays with highly active heterointerfaces for water oxidation in alkali media. (20th January 2023) - Liu, Tianpeng; Liu, Wenhao; Ma, Mengyao; Guo, Linke; Cui, Rong; Cheng, Daojian; Cao, Dong
Highlights: Nickel phosphide and nickel oxide hydroxide heterostructure is fabricated. NiVP shows excellent activity for water oxidation in alkali media. Synergistic effects between heterostructures improve the catalytic performance. Abstract: Developing low-cost, ultra-stable, and active non-noble metal catalyst is distinctly indispensable for oxygen evolution reaction (OER). Herein, an ordered nickel vanadium phosphide (NiVP) nanoarray catalyst with abundant interfaces was successfully constructed via a facile multi-step strategy. Notably, the interface-rich NiVP nanoarray shows excellent activity for OER in the alkaline solution, which just requires a low overpotential of 253 mV at current density of 10 mA cm −2 and displays a Tafel slope of 78 mV dec −1, obviously outperforms commercial RuO2 . Further studies confirmed that the heterojunction interface between nickel phosphide (Ni2 P) and nickel oxyhydroxide acts as the main role for OER, which could optimize the adsorption of oxygen intermediates due to the electron migration. Moreover, heterointerfaces are also beneficial to the exposure of active sites during OER, effectively accelerating the reaction kinetics. This work develops a novel electrocatalyst with superior activity for OER, contributing to the development of water splitting driven by renewable energy. Graphical abstract: Image, graphical abstract